Προστασία και διαχείριση ενάλιας πολιτιστικής κληρονομιάς και θαλάσσιων οικοσυστημάτων: ο υποθαλάσσιος τουρισμός ως παράγων ανάπτυξης ειδικών περιοχών – χωρικών ενοτήτων - Τσούτσου, Χριστίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αρχιτεκτόνων Μηχανικών, 2016)
Since the 1990’s various studies for the South Aegean Region indicate that the sea element, which is so important for other economic activities such as fisheries and recreation, has not been properly studied and analysed in relation to other potentially interesting and prosperous activities. These can support and contribute further to the development of the Region socially, economically and environmentally.